Algerian Female Engineers Challenging The Masculine Culture Of Engineering: A Look At Gender And Prevailing Barriers - Imen Ratoul; Mustapha Boudjellal (The Journal of Studies in Language, Culture and Society, 2021)
The present article focuses on women’s integration into male-dominated domain to offer insights into Algerian females’ experiences in engineering as male-dominated occupation. It aims to identify some of the many barriers imposed by cultural assumptions on female workers and engineers in particular. To fit the above need, this study is meant for the examination and analysis measured with a critical approaches to fully examine and identify the historical nature of engineering, thus, the research has to bring together well known methodological frameworks such as critical discourse analysis as well as the tenets of social constructionist approach which serves to fully understand the problem of women in engineering with men and the taken-for-granted masculinities of engineering.